2008
DOI: 10.1128/aem.01948-08
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Clostridium beijerinckii NCIMB 8052 and the Hyper-Butanol-Producing Mutant BA101 during the Shift from Acidogenesis to Solventogenesis

Abstract: Clostridium beijerinckii is an anaerobic bacterium used for the fermentative production of acetone and butanol. The recent availability of genomic sequence information for C. beijerinckii NCIMB 8052 has allowed for an examination of gene expression during the shift from acidogenesis to solventogenesis over the time course of a batch fermentation using a ca. 500-gene set DNA microarray. The microarray was constructed using a collection of genes which are orthologs of members of gene families previously found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 37 publications
6
45
2
Order By: Relevance
“…Evidence suggests that alcohol tolerance is composed of an extensive and complex set of responses, not just those responsible for repairing the membrane. Transcriptomic and proteomic analyses have revealed increased transcripts and proteins responsible for cell wall biogenesis, osmoregulation, heat shock proteins, carbohydrate transport, glycolytic enzymes, protein turnover, and in some cases sporulation during alcohol exposure (19,30,38,39,42). Therefore, the generation of more tolerant organisms will have to involve modifications that not only maintain membrane fluidity, but also maintain redox, osmotic, and ion homeostasis, as well as protein structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that alcohol tolerance is composed of an extensive and complex set of responses, not just those responsible for repairing the membrane. Transcriptomic and proteomic analyses have revealed increased transcripts and proteins responsible for cell wall biogenesis, osmoregulation, heat shock proteins, carbohydrate transport, glycolytic enzymes, protein turnover, and in some cases sporulation during alcohol exposure (19,30,38,39,42). Therefore, the generation of more tolerant organisms will have to involve modifications that not only maintain membrane fluidity, but also maintain redox, osmotic, and ion homeostasis, as well as protein structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…After the donor plasmid was cured, the positive knockout mutant strains were cultivated anaerobically in P2 medium (24), and spore stocks were harvested as described earlier (25). Spores were heat shocked at 80°C for 10 min, followed by cooling on ice for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The gene expression analyses of C. acetobutylicum 176,177 and C. beijerinckii, 150 revealed that during the acidogenic phase, two fold increase in the expression of the pta and ack genes responsible for acetate formation was observed.…”
Section: Phase Transition Regulation From Acidogenesis To Solventogenmentioning
confidence: 99%
“…150 A transcriptome analysis for the evaluation of gene expression levels during phase transition in C. acetobutylicum with phosphatelimited continuous cultures showed that the expression levels of the adhE1, ctfA-ctfB, and adc genes were induced during the solventogenic phase (pH 4.5) compared with the acidogenic phase (pH 5.8). 178 It was also found that, under phosphate-limited continuous culture conditions, the adhE1 and adhE2 genes were antagonistically regulated.…”
Section: Phase Transition Regulation From Acidogenesis To Solventogenmentioning
confidence: 99%
See 1 more Smart Citation